2009
DOI: 10.1002/jbm.b.31325
|View full text |Cite
|
Sign up to set email alerts
|

Postimplantation pressure testing and characterization of laser bonded glass/polyimide microjoints

Abstract: The stability of the laser bonded titanium coated glass/polyimide microjoints were studied in vivo by implanting on a rat brain surface for 10 days. In the current state, the strength of the joints were measured by a specially designed instrument called "pressure test" equipment where the samples were subjected to a variable pressure load (using high pressure nitrogen) controlled by a pressure regulator. The strength of the joints seems to degrade by about 28% as a result of soaking in rat brain. The bond degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…cm 3 /s, and it was concluded that the polyimide-titanium seal was nearhermetic. Post-implantation assessment after implant in a rat brain for 10 days showed that hermeticity was maintained, however, a 28% reduction in bond strength was observed [111]. The group concluded that the seals could be effective for short-term implants and that further optimisation was required for long-term implantation.…”
Section: Application Of Welding Methods For Polymer Based Encapsulationmentioning
confidence: 93%
“…cm 3 /s, and it was concluded that the polyimide-titanium seal was nearhermetic. Post-implantation assessment after implant in a rat brain for 10 days showed that hermeticity was maintained, however, a 28% reduction in bond strength was observed [111]. The group concluded that the seals could be effective for short-term implants and that further optimisation was required for long-term implantation.…”
Section: Application Of Welding Methods For Polymer Based Encapsulationmentioning
confidence: 93%
“…Mian et al used transmission laser welding of titanium-coated glass-polyimide joints to demonstrate that optical fiber laser-welded joints provided stronger bonds than diode laser-welded joints [29]. In a recent study, Mian et al showed that laser-welded, titanium-coated, glass-polyimide micro-joints lost 28% of joint strength after incubating with rat brain tissue for 10 days [30]. Their work indicates that additional efforts are needed for the use of polymer laser welding in medical implants.…”
Section: Laser Processing Of Biomaterialsmentioning
confidence: 99%
“…29 In a recent study, Mian et al showed that laserwelded, titanium coated, glass-polyimide microjoints lost 28% of joint strength after incubating with rat brain tissue for 10 days. 30 Their work indicates that additional efforts are needed for use of polymer laser welding in medical implants.…”
Section: Laser Processing Of Biomaterialsmentioning
confidence: 99%